Transmission of knowledge and representation: critical contributions from the book "Psychic Development" by Alexis Leontiev - Mériti de Souza (Universidade Federal de Santa Catarina, 2018)
This work is a theoretical study that seeks from established limits to analyze concepts of representation and language present in the book The Psychic Development by Alexis Leontiev, considering the relations of these ideas with practices of knowledge transmission. The interest lies in educational contexts considering that in most of the pedagogical strategies elaboration prevails presuppositions on language and representation supported by the formal logic. The book analysis is carried out as a resource, and it privileges the concepts of representation and language concomitant with the critical reading on such resources and the activity of knowledge transmission, in the modern scenario.